INTEGRATING INFORMATION COMMUNICATION TECHNOLOGY IN ENGLISH LANGUAGE TEACHING - Joko Prayudha. S; Nabila Maratus Salihah; Ami Pradana (English Education Study Program STKIP PGRI Pacitan, 2023)
The development of information and communication technology is what most people look forward to, including technological advances in the field of education which are very useful for teachers and students. Teachers can apply the use of technology in learning English to help and facilitate teaching and learning activities and encourage students to actively participate in learning. This study aims to explain the importance of applying technology in teaching English. The method used in this research is qualitative through a literature study approach. Data was obtained through collecting references and materials related to the use of ICT in learning and teaching English. After the data is obtained, the data is presented based on predetermined boundaries. The results of the study show that the use of technology in teaching English can make the learning atmosphere more enjoyable, students can freely get and do assignments and can access more learning resources. In addition, by utilizing information and communication technology students become more creative and motivated to be actively involved in teaching and learning activities so that it is very necessary for English teachers to regularly integrate the use of communication and information technology in learning English.